Working capital management, firm performance and earnings management of public listed companies in Malaysia and Thailand - Mohd Ashhari, Zariyawati (2012)
Long term financial decision particularly capital structure, dividends and firm valuation decision were established focusing in the area of corporate finance. However, this pattern has changed in recent years. Most of the researchers have diverted their focus to short term financial research, which is working capital management. This change occurs because the researchers have adopted and believed the theory of Smith (1973). This theory could explain the reasons why many firms are facing financial problems and cease their operation during Asian financial crisis in 1997/1998. Smith (1973) suggested that a business will fail due to the lack of emphasis on working capital in financial decision making. However, working capital engaged in daily business operations only. It is a short-term investment in nature,hence playing an important role in firm’s financial decision to ensure that firm can survive in the long term period. Previous researches on working capital management have been done in developed countries, such as United States and United Kingdom. However, financial markets in developed countries differ from developing countries such as Malaysia and Thailand. In developed countries, firm’s share widely dispersed share ownership. Meanwhile, most of the listed firms are controlled by a few shareholders (individual or institutions) in developing countries. Furthermore, previous researches mainly focused on the relationship between working capital management and firm’s performance. This study examines the behaviour of working capital management for firms in Malaysia and Thailand. Panel data of 244 firms from Malaysia and 149 firms from Thailand for the period of 1994 to 2007 were used in this study. Generalized Moment Method (GMM) model is conducted to achieve the objective of the study. The first objective is to determine the factors of working capital management. The results showed firm-characteristic, corporate governance and macroeconomics are important factors which influencing working capital management. For the second objective, this study investigates the effect of working capital management on firm performance. The results showed that firms’ working capital management in Malaysia have negative significant effect on all measurement (return on assets, Tobin's-q and market to book value). Empirical evidence also shows that no relationship exist between working capital management and firm performance before the Asian financial crisis. Results for second objective of Thailand are consistent with Malaysia. This result reveals that manager of firms do not manage working capital efficiently before the crisis. Consequently, investment in working capital management does not contribute to firm performance. However, after the crisis in demonstrate that manager had learned from Asian financial crisis. They put more effort to establish efficient working capital management. Hence, firm performance is increased after the crisis. Further, the third objective of this study is to examine the involvement of earnings management in working capital management of firms in Malaysia and Thailand. This study found that earnings management has a significant relationship with firm’s working capital management. However, the involvement of earnings management in the firm’s financial decision is a common practice for both countries. Therefore, managers should put more attention in managing working capital in order to avoid from experiencing financial difficulties which consequently will result in termination of business operations. As a whole, the behaviour of working capital management in Malaysia and Thailand are akin to each other. The determinant factors of working capital management for both countries have changed after the Asian financial crisis compared to the period prior to the financial crisis. Findings showed that working capital management affects firm performance and the effect is obvious after financial crisis. This study also revealed the existence of earnings management in firm’s working capital management. As a conclusion of this study, managers of firms in both countries had learned from past experiences. After the Asian financial crisis, they gave more emphasis in working capital management in order to be more efficient and consequently increase firms’ performance.